Synthesis, function, and regulation of sterol and nonsterol isoprenoids - Faulkner, Rebecca; Jo, Youngah (Frontiers in Molecular Biosciences, 2022)
Cholesterol, the bulk end-product of the mevalonate pathway, is a key component of cellular membranes and lipoproteins that transport lipids throughout the body. It is also a precursor of steroid hormones, vitamin D, and bile acids. In addition to cholesterol, the mevalonate pathway yields a variety of nonsterol isoprenoids that are essential to cell survival. Flux through the mevalonate pathway is tightly controlled to ensure cells continuously synthesize nonsterol isoprenoids but avoid overproducing cholesterol and other sterols. Endoplasmic reticulum (ER)-localized 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase (HMGCR), the rate limiting enzyme in the mevalonate pathway, is the focus of a complex feedback regulatory system governed by sterol and nonsterol isoprenoids. This review highlights transcriptional and post-translational regulation of HMGCR. Transcriptional regulation of HMGCR is mediated by the Scap-SREBP pathway. Post-translational control is initiated by the intracellular accumulation of sterols, which causes HMGCR to become ubiquitinated and subjected to proteasome-mediated ER-associated degradation (ERAD). Sterols also cause a subfraction of HMGCR molecules to bind the vitamin K2 synthetic enzyme, UbiA prenyltransferase domain-containing protein-1 (UBIAD1). This binding inhibits ERAD of HMGCR, which allows cells to continuously synthesize nonsterol isoprenoids such as geranylgeranyl pyrophosphate (GGpp), even when sterols are abundant. Recent studies reveal that UBIAD1 is a GGpp sensor, dissociating from HMGCR when GGpp thresholds are met to allow maximal ERAD. Animal studies using genetically manipulated mice disclose the physiological significance of the HMGCR regulatory system and we describe how dysregulation of these pathways contributes to disease.